Parenthood in intensified documentation and assessment practice – with the focus on the home-school relation in Sweden - Vallberg Roth, Ann-Christine (International Journal about Parents in Education, 2023)
The study seeks to describe and analyse parenthood in intensified documentation and assessment practice, with the focus on the home-school relation in Sweden. The research is based on fieldwork on the Internet. What currents of thought and dimensions of parenthood can be detected? What is considered in assessments and documentation of children? Who assesses whom? Whose interests can be interpreted as being involved in parenthood? The sample consists of material from two Internet sites, a total of about 120 pages. The unit of analysis in the study consists of online text-based communication initiated by parents in 2008–2009. Textual analysis was performed with an extended hermeneutic approach. The material from the Internet includes threads dealing with personal development interviews, individual development plans with written assessments, and standardized test and observation material. In the material there are examples of teachers assessing children, and examples of parents assessing teachers, other parents, and themselves. Four dimensions of parenthood emerge, which can be described as policy-related, evidence-related, market- and media-oriented, and experience-based. The dimensions that indicate which interests are involved can be interpreted as being either concordant and interwoven or contradictory. The study contributes to a greater understanding, qualifies the discourse, and offers alternative interpretations of what is at stake in an intensified documentation and assessment practice.